1999
DOI: 10.1038/sj.cgt.7700051
|View full text |Cite
|
Sign up to set email alerts
|

Murine interferon-α1 gene-transduced ESb tumor cells are rejected by host-mediated mechanisms despite resistance of the parental tumor to interferon-α/β therapy

Abstract: The highly metastatic ESb tumor is totally resistant to murine interferon-␣/␤ (IFN-␣/␤) therapy, regardless of the number of cells injected or the route of inoculation. In contrast, as we show herein, mouse IFN-␣ 1 -transduced ESb tumor cells were inhibited markedly when injected subcutaneously into immunocompetent mice. IFN-producing ESb tumor rejection was mediated by the immune system, because these tumor cells grew normally in immunosuppressed mice. Tumor regression was accompanied by extensive necrosis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…8 Notably, in a recent study in which we specifically selected a highly metastatic mouse tumor resistant to therapy with large doses of IFN-␣/␤, we found that the genetically modified tumor cells expressing IFN-␣ were efficiently rejected by host-mediated mechanisms when injected into immunocompetent syngeneic mice, suggesting that there might be some advantages in transducing this cytokine gene with respect to the conventional therapy. 13 IFN-␣ gene therapy using gene-modified tumor cells or fibroblasts as well as viral vectors has been shown to suppress effectively the growth of mouse 7,12 or human tumors implanted into nude mice. [14][15][16][17] In some of these studies, a better therapeutic effect was achieved when the treatment of tumorbearing mice with IFN-␣-expressing cells was combined with chemo-or chemoimmunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…8 Notably, in a recent study in which we specifically selected a highly metastatic mouse tumor resistant to therapy with large doses of IFN-␣/␤, we found that the genetically modified tumor cells expressing IFN-␣ were efficiently rejected by host-mediated mechanisms when injected into immunocompetent syngeneic mice, suggesting that there might be some advantages in transducing this cytokine gene with respect to the conventional therapy. 13 IFN-␣ gene therapy using gene-modified tumor cells or fibroblasts as well as viral vectors has been shown to suppress effectively the growth of mouse 7,12 or human tumors implanted into nude mice. [14][15][16][17] In some of these studies, a better therapeutic effect was achieved when the treatment of tumorbearing mice with IFN-␣-expressing cells was combined with chemo-or chemoimmunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Using the poorly immunogenic, highly metastatic TS/A mammary adenocarcinoma, it was shown that injection of IFN‐α1‐secreting TS/A cells into immunocompetent mice resulted in host‐dependent rejection of the genetically modified tumor cells, mostly mediated by CD8 + T cells, and in the development of protective immunity against the parental TS/A tumor 6 . In a subsequent study, 7 the highly metastatic lymphoma ESb was chosen for IFN‐α gene transfer especially because of its resistance to IFN‐α/β therapy. In spite of its IFN‐resistant phenotype, ESb tumor cells expressing IFN‐α were efficiently rejected by host‐mediated mechanisms, 7 suggesting a possible advantage in transducing this cytokine gene into tumor cells as compared with systemic administration.…”
Section: Lessons Learned From Studies In Mouse Tumor Modelsmentioning
confidence: 99%
“…In a subsequent study, 7 the highly metastatic lymphoma ESb was chosen for IFN‐α gene transfer especially because of its resistance to IFN‐α/β therapy. In spite of its IFN‐resistant phenotype, ESb tumor cells expressing IFN‐α were efficiently rejected by host‐mediated mechanisms, 7 suggesting a possible advantage in transducing this cytokine gene into tumor cells as compared with systemic administration. The findings that rejection of IFN‐α‐producing tumor cells conferred protection against a subsequent challenge with parental tumor cells, 4,6 and of the importance of CD8 + T cells for the rejection of IFN‐α‐producing TS/A tumors 6 implied that memory T cells were generated upon exposure of mice to the IFN‐α‐producing cells.…”
Section: Lessons Learned From Studies In Mouse Tumor Modelsmentioning
confidence: 99%
“…A LLC se mostrou sensível a transferência gênica de p19 e não p53. Tal observação vai ao encontro da bibliografia que sugere que em linhagens derivadas de LLC a super-regulação de MDM2 desenpenha um papel importante na regulação de p53 (Rizzo, Soddu et al 1993) (Rizzo, Soddu et al 1993;Qin, Tao et al 1998;D'Agostino, Arico et al 1999;Lu, Fidler et al 1999;Rozera, Carlei et al 1999;Rozera, Mecchia et al 1999).…”
Section: Discussão E Perspectivasunclassified